2023
DOI: 10.1186/s10195-023-00688-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced knee laxity and failure rate following anterior cruciate ligament reconstruction compared with repair for acute tears: a meta-analysis

Abstract: Background Following anterior cruciate ligament (ACL) tears, both repair and reconstruction may be performed to restore joint biomechanics and proprioception. The present study compared joint laxity, patient-reported outcome measures (PROMs), and rate of failure following primary repair versus reconstruction for ACL ruptures. Methods This meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Pubme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Traditionally, ACL tears in skeletally immature patients were treated conservatively with bracing and physiotherapy, as ACL reconstruction techniques could damage the growing epiphyseal plates, potentially leading to growth disturbances, including leg-length discrepancy or angular deformities [5,6]. However, instability sensation might persist and soft tissue injuries might occur following conservative management [7,8]. Different surgical techniques for ACL reconstruction to avoid epiphyseal plate injuries have been described [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, ACL tears in skeletally immature patients were treated conservatively with bracing and physiotherapy, as ACL reconstruction techniques could damage the growing epiphyseal plates, potentially leading to growth disturbances, including leg-length discrepancy or angular deformities [5,6]. However, instability sensation might persist and soft tissue injuries might occur following conservative management [7,8]. Different surgical techniques for ACL reconstruction to avoid epiphyseal plate injuries have been described [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) reconstruction improves knee laxity [20,22]; however, previous studies have reported that quadriceps muscles were still weak after surgery [5, Extended author information available on the last page of the article 18]. Quadriceps strength recovery after ACL reconstruction was associated with postoperative hop performance [4,6,34], self-reported knee function [6,14,36], patellar cartilage injury [10,31], and return to preinjury sports [1,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…11,15 In addition, ACL repair preserves the proprioceptive function of the native ligament and the range of motion (ROM) of the knee and prevents donor site morbidity. 16,22,28 Although limited research on RTS after ACL primary repair is available, a recent study including 60 patients with a minimum 2-year follow-up demonstrated a 60% rate of return to preinjury activity levels. 26 However, to the best of our knowledge, specific research focusing on return to soccer after ACL repair is lacking.…”
mentioning
confidence: 99%